Media and Political Power in Indonesia: A Critical Discourse Analysis of CNN Indonesia's Presidential Club Coverage - Prayogo, Moh. Dey; Fikri, Sultoni (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
This research focuses on the news published by cnnindonesia.com, which highlights the pro and contra issues surrounding the idea of establishing the Presidential Club. This topic serves as the focal point for analysis using Van Dijk's Critical Discourse Analysis theory. This research aims to provide a critical analysis of the coverage regarding the discourse on the formation of the Presidential Club. Through a critical discourse analysis approach, this study will delve deeper into how various narratives, representations, and political interests are reflected in the news coverage. The analysis will emphasize how power and control over knowledge are reproduced through the news text, as well as how resistance and opposition to the idea are reflected in the presented narratives. Through this approach, it is hoped that this research will offer profound insights into the political dynamics and power relations associated with the discourse on establishing institutions like the Presidential Club.